User-Generated Content as a Brand Image Builder: An Explanatory Study on Instagram's JackArmy Fashion Brand Image - Gobel, Elrick; Mulyani, Henny Sri; Gemiharto, Ilham (Ilomata International Journal of Social Science, 2024)
Instagram has become a crucial platform for fashion businesses to interact with consumers and build brand image. User-generated content (UGC) plays a significant role in this process. This research examines the effect of social interaction and technical feature attractiveness of UGC advertising on Instagram on JackArmy's brand image. This study employs an explanatory survey involving 293 JackArmy's Instagram account followers. Data were analyzed using Partial Least Squares (PLS) with SmartPLS 3.0 software. The findings indicate that social interaction and technical feature attractiveness of UGC advertising positively influence JackArmy's brand image. This research highlights the importance of UGC in digital marketing strategies, particularly for fashion businesses. Social interaction and content quality of UGC are proven to be critical factors in building a positive brand image among consumers.